Route to benzimidazol-2-ones via decarbonylative ring contraction of quinoxalinediones: application to the synthesis of flibanserin, A drug for treating hypoactive sexual desire disorder in women and marine natural product hunanamycin analogue - Shingare, Rahul D.; Kulkarni, Akshay S.; Sutar, Revannath L.; Reddy, D. Srinivasa (ACS Omega, 2017)
A simple and practical method to access a variety of benzimidazol-2-ones is reported here. A series of N-alkylsubstituted benzimidazol-2-ones were synthesized by decarbonylative ring contraction starting from corresponding quinoxalinediones for the first time. The utility of the method has been demonstrated by synthesizing recently approved controversial drug flibanserin (Addyi) and a urea analogue of marine antibiotic natural product hunanamycin-A.

Evaluating antimalarial efficacy by tracking glycolysis in Plasmodium falciparum using NMR spectroscopy - Shivapurkar, Rupali; Hingamire, Tejashri; Kulkarni, Akshay S.; Rajamohanan, P. R.; Reddy, D. Srinivasa; Shanmugam, Dhanasekaran (Scientific Reports, 2018)
Glucose is an essential nutrient for Plasmodium falciparum and robust glycolytic activity is indicative of viable parasites. Using NMR spectroscopy, we show that P. falciparum infected erythrocytes consume similar to 20 times more glucose, and trophozoites metabolize similar to 6 times more glucose than ring stage parasites. The glycolytic activity, and hence parasite viability, can be measured within a period of 2 h to 5 h, using this method. This facilitates antimalarial bioactivity screening on ring and trophozoite stage parasites, exclusively. We demonstrate this using potent and mechanistically distinct antimalarial compounds such as chloroquine, atovaquone, cladosporin, DDD107498 and artemisinin. Our findings indicate that ring stage parasites are inherently more tolerant to antimalarial inhibitors, a feature which may facilitate emergence of drug resistance. Thus, there is a need to discover novel antimalarial compounds, which are potent and fast acting against ring stage parasites. The NMR method reported here can facilitate the identification of such molecules.

Targeted phenotypic screening in plasmodium falciparum and toxoplasma gondii reveals novel modes of action of medicines for malaria venture malaria box molecules - Subramanian, Gowtham (mSphere, 2018)
The Malaria Box collection includes 400 chemically diverse small molecules with documented potency against malaria parasite growth, but the underlying modes of action are largely unknown. Using complementary phenotypic screens against Plasmodium falciparum and Toxoplasma gondii, we report phenotype-specific hits based on inhibition of overall parasite growth, apicoplast segregation, and egress or host invasion, providing hitherto unavailable insights into the possible mechanisms affected. First, the Malaria Box library was screened against tachyzoite stage T. gondii and the half-maximal effective concentrations (EC50s) of molecules showing ≥80% growth inhibition at 10 µM were determined. Comparison of the EC50s for T. gondii and P. falciparum identified a subset of 24 molecules with nanomolar potency against both parasites. Thirty molecules that failed to induce acute growth inhibition in T. gondii tachyzoites in a 2-day assay caused delayed parasite death upon extended exposure, with at least three molecules interfering with apicoplast segregation during daughter cell formation. Using flow cytometry and microscopy-based examinations, we prioritized 26 molecules with the potential to inhibit host cell egress/invasion during asexual developmental stages of P. falciparum. None of the inhibitors affected digestive vacuole integrity, ruling out a mechanism mediated by broadly specific protease inhibitor activity. Interestingly, five of the plasmodial egress inhibitors inhibited ionophore-induced egress of T. gondii tachyzoites. These findings highlight the advantage of comparative and targeted phenotypic screens in related species as a means to identify lead molecules with a conserved mode of action. Further work on target identification and mechanism analysis will facilitate the development of antiparasitic compounds with cross-species efficacy.

Total synthesis of an anticancer natural product (+/-)-peharmaline A and its analogues - Kulkarni, Akshay S.; Shingare, Rahul D.; Dandela, Rambabu; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2018)
First total synthesis of a rare beta-carboline-vasicinone hybrid alkaloid (+/-)-peharmaline A has been accomplished in just 3 steps starting from known compounds. Stereoselective Pictet-Spengler reaction to nitrogenated tertiary carbon center and one-pot construction of the tricyclic skeleton of vasicinone are the highlights of present synthesis. We have also synthesized structurally close analogues of the natural product by following the developed route.

Targeted phenotypic screening in plasmodium falciparum and toxoplasma gondii reveals novel modes of action of medicines for malaria venture malaria box molecules (vol 3, e00534-17, 2018) - Subramanian, Gowtham; Belekar, Meenakshi A.; Shukla, Anurag; Tong, Jie Xin; Sinha, Ameya; Chu, Trang T. T.; Kulkarni, Akshay S.; Preiser, Peter R.; Reddy, D. Srinivasa; Tan, Kevin S. W.; Shanmugam, Dhanasekaran; Chandramohanadas, Rajesh (MSphere, 2019)

Identification of a novel series of potent organosilicon mosquito repellents - Kulkarni, Akshay S.; Ramesh, Remya; Walia, Safal; Sayyad, Shahebaz I.; Gathalkar, Ganesh B.; Balamkundu, Seetharamsing; Joshi, Manali; Sen, Avalokiteswar; Reddy, D. Srinivasa (ACS Omega, 2021)
Mosquito control by personal protection is one of the most efficient ways of curtailing deadly diseases such as malaria and dengue with the potential to save millions of lives per year. DEET (N,N-diethyl-3-methyl benzamide) is currently considered as the gold standard for mosquito repellents, being used for the past several decades. Control by DEET, however, is being threatened by emerging resistance among mosquitoes. To address this concern and also to improve protection times, we synthesized a novel series of 25 silicon-containing acyl piperidines using acid–amine coupling protocol and tested their activity against Aedes aegypti in mosquito-repellent assays. Several compounds from this series appear to possess good mosquito-repellent properties. Most notably, at 0.5 mg/cm2 concentrations, the mean protection time for NDS100100 was 756 min, which was higher than that of DEET (616 min). The details of design, synthesis, and biological evaluation are discussed herein.

One-pot oxidation of secondary alcohols to alpha-hydroxy ketones: application to synthesis of oxoaplysinopsin D, E, F, & G - Kulkarni, Akshay S.; Ramesh, Eagala; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2021)
A simple one-pot transformation of secondary alcohols to alpha-hydroxy ketones using pyridinium dichromate (PDC) in DMF has been developed and substrate scope tested with 25 compounds of hydantoin derivatives. Using this method, we have devised a common dihydroxy intermediate and synthesized four natural products oxoaplysinopsins D, E, F, and G for the first time.
Keywords: alpha-Hydroxylation; Hydantoin; Natural product; Oxoaplysinopsin; Retro-aldol

Identification of new modulator of DNA repairing pathways based on natural product (±)-peharmaline A - Kulkarni, Akshay S.; Dash, Anshurekha; Shingare, Rahul D.; Chand, Jagdish; Manhas, Diksha; Singh, Aman; Nandi, Utpal; Goswami, Anindya; Reddy, D. Srinivasa (Bioorganic & Medicinal Chemistry, 2023)
The complex heterogenic environment of tumour mass often leads to drug resistance and facilitate chemo insensitivity triggering more malignant phenotypes among cancer patients. Major DNA-damaging cancer drugs have been consistently proven unsuccessful in terms of elevating chemo-resistance. (& PLUSMN;)-peharmaline A, a hybrid natural product isolated from seeds of Peganum harmala L. possesses significant cytotoxic activities. Herein, we have described the design, and synthesis of a novel library of close and simplified analogues around the anticancer natural product (& PLUSMN;)-peharmaline A and investigated their cytotoxic activities, which led to the identification of three structurally simplified lead compounds exhibiting better potency than parent natural product. Among them, demethoxy analogue of peharmaline A was further investigated for its anticancer potential eliciting demethoxy analogue as potent DNA-damage inducing agent attenuating the expression of the proteins responsible for the DNA damage repair. Therefore, this demethoxy analogue warrants detailed investigations for the confirmations of the molecular mechanism-based studies responsible for its anticancer activity.
Keywords: DNA damage; EMT; Pictet; Spengler reaction; Structure-activity relationship; Total synthesis

Interplay between genotoxic stress and STING activation in cellular senescence and inflammatory responses - Dash, Anshurekha; Kulkarni, Akshay S.; Irshad, Faisal; Masal, Dattatraya P.; Manhas, Diksha; Nandi, Utpal; Reddy, D. Srinivasa; Goswami, Anindya (International Immunopharmacology, 2025)
STING pathway is activated by endogenous or exogenous DNA damage and is known to trigger cell-intrinsic innate immunity. In this study, we demonstrated that the Peharmaline analog NDS101781 is a potent genotoxic molecule to trigger cellular senescence via innate immune-responsive STING activation. We found NDS101781 consistently modulated the expression of DDR markers including gamma-H2AX, Rad51, PARP1, ATM and MRE11 in breast cancer cells with concomitant amplification in the hallmarks of senescence along with STING signaling mediators which is intricately involved in NDS101781-mediated senescence activation as evidenced by significant reduction in the senescent population in si-TMEM173-transfected cells. In vitro findings proclaimed that STING activation by NDS101781 is crucial for p21-mediated senescence augmentation, a process regulated by ATM and p53 via a pathway independent of cGAS. Although STING is activated by both canonical and non-canonical manner, our mechanistic findings indicated that ATM played a crucial role in early activation of NDS101781 driven STING signaling via p53 activation and stimulation of pTBK1, NF-kappa B, and p-IRF3, through a non-canonical cascade in cGAS-independent mechanism. The results also indicated that interference of canonical and non-canonical STING activation, responsible for NF-kappa B stimulation leading to IL-6 generation. Intriguingly, the inhibition of ATM diminished senescence hallmarks; however, suppression of ATM as well as p21 neutralization triggered apoptotic cascade and thus regulating the SASP factors. However, transient knockdown of p21 moderately instigated the apoptotic mediators underscoring that NDS101781 mediated senescence induction delayed programmed cell death under intact p21 conditions. Moreover, pharmacokinetics of NDS101781 confirmed its excellent half-life in a preclinical model and in vivo studies confirmed that NDS101781 significantly inhibited tumor growth in a syngeneic aggressive 4T1-p53 breast cancer model.
Keywords: ATM; IL-6; Peharmaline; Senescence; STING

Silicon incorporated tacrine: design, synthesis, and evaluation of biological and pharmacokinetic parameters - Kulkarni, Akshay S.; Ramana, Sreenivasa Rao; Nuthakki, Vijay K.; Bhatt, Shipra; Jamwal, Ashiya; Nandawadekar, Laxman D.; Jotshi, Anshika; Kumar, Ajay; Nandi, Utpal; Bharate, Sandip B.; Reddy, D. Srinivasa (RSC Medicinal Chemistry, 2025)
Tacrine, an orally bioavailable cholinesterase inhibitor, was previously used to treat Alzheimer's disease but was withdrawn due to hepatotoxicity. The unique structural features of tacrine have once again captured the interest of medicinal chemists. However, the blood-brain barrier (BBB) permeability hampered the development of the majority of its new analogs. Herein, we employed a silicon switch approach for improving the BBB permeability of CNS drugs with tacrine as a tool compound. The replacement of C2 methylene of tacrine with dimethyl silicon yielded `sila-tacrine' that inhibits acetylcholinesterase as well as butyrylcholinesterase with IC50 values of 3.18 and 6.09 mu M, respectively. Sila-tacrine competitively inhibits acetylcholinesterase while it is a non-competitive inhibitor of butyrylcholinesterase. The molecular docking results corroborated with the in vitro cholinesterase inhibition activity of tacrine vs. sila-tacrine. Sila-tacrine demonstrated metabolic stability in HLM and MLM and exhibited superior plasma exposure in an oral pharmacokinetic study in Swiss albino mice. However, tissue distribution studies revealed lower-than-expected brain levels due to efflux pump-mediated transport. This study offers a proof-of-concept for the silicon switch approach in improving the BBB permeability of CNS-active compounds.